Application of efgartigimod in Chinese patients with myasthenia gravis: a single-center real-world prospective study - Geke Zhu; Han Zhou; Wanying Wang; Yongbo Ma; Xiangtao Nie; Wenjing Qi; Lei Hao; Xiuming Guo (Therapeutic Advances in Neurological Disorders)
Background: China has a large number of myasthenia gravis (MG) patients, creating an urgent need for rapid and tolerable treatment options. As the first-approved Fc receptor antagonist, efgartigimod has bright prospects for treating MG. However, real-world evidence on its application within the Chinese MG population are limited. Objective: This study aims to evaluate the rapid efficacy and safety of efgartigimod in Chinese MG population. Design: This single-center prospective study enrolled Chinese MG patients aged 18 and older who were treated with efgartigimod, classified as Myasthenia Gravis Foundation of America I–IV, with a baseline Myasthenia Gravis Activities of Daily Living (MG-ADL) score of at least 4. Methods: Patients received efgartigimod at a dose of 10 mg/kg infused once weekly for 4 weeks. During the treatment, the corticosteroids dosage could be adjusted as appropriate or the non-steroidal immunosuppressive therapies (NSISTs) added. Prior to each infusion, patients’ MG-ADL scores, IgG levels, and routine laboratory tests were evaluated, while also recording the prednisone tapering and any adverse events occurring during the treatment. Results: Twenty five Chinese MG patients were enrolled between November 2023 and June 2024, including 3 with ocular MG (OMG) and 22 with generalized MG (GMG). During the 8-week follow-up, in GMG patients, whether positive for acetylcholine receptor (AChR) or muscle-specific tyrosine kinase (MuSK) antibodies, the overall efficacy was significant. Within one treatment cycle, 18 (82%) patients showed a reduction of at least 2 points in MG-ADL scores and sustained for at least 4 weeks, and 6 (27%) attained minimal symptom expression (MSE) and sustained for at least 4 weeks. Only 1 patient experienced exacerbation. Among OMG patients, 1 achieved MSE within the treatment cycle, while 2 showed minor improvements. Patients who added tacrolimus concurrently with efgartigimod did not achieve better improvement in MG-ADL scores compared to others. The average reduction in prednisone dosage was 27.4%. Only one patient experienced transient vomiting and diarrhea, with no serious adverse reactions reported. Conclusion: This study confirmed the short-term efficacy and safety of efgartigimod in Chinese MG patients. However, in clinical practice, careful consideration is needed regarding its application in OMG and whether to add NSISTs regimen during the treatment. Efgartigimod could potentially serve as an alternative to long-term corticosteroids therapy.